Macroprudential Regulation of Credit Booms and Busts : The Experience of the National Bank of the Republic of Macedonia - Celeska, Frosina; Gligorova, Viktorija; Krstevska, Aneta (2012)
This paper provides an overview of the macroprudential measures undertaken by the National Bank of the Republic of Macedonia to prevent further deterioration of the systemic risk and to promote resilience of the banking system. The measures were generally aimed at addressing the time dimension of the systemic risk and were intended to protect the banking system against the increase of credit risk arising from the credit boom. The paper also outlines the future challenges facing financial regulation and supervision, as well as the most important quantitative and qualitative impacts of the utilized macroprudential measures.